Beetle diversity in dead wood is lower in non‐native than native tree species, especially those more distantly related to native species. Issue 1 (4th November 2022) - Kärvemo, Simon; Schroeder, Martin; Ranius, Thomas
Abstract: Non‐native tree species are widely used in forest plantations. This may have negative consequences for biodiversity. Hitherto, most studies have compared species diversity between native and non‐native forest stands, which makes it difficult to separate the impact of tree species per se from stand characteristics. Our study, conducted in the south of Sweden, compares saproxylic beetle diversity across different nutritional groups, in dead wood of two native and four non‐native tree species in a block design after one and three seasons. Such an approach allows analysis of the impact of non‐native tree species per se. Mean species richness (± SD) per log was lower in non‐native than in native tree species (non‐native trees: lodgepole pine: 10.7 (± 5.3); Sitka spruce: 8.5 (± 4.3), Douglas fir: 7.1 (± 4.3), Japanese larch 9.4 (± 4.6); native trees: Norway spruce: 12.0 (± 6.0), Scots pine: 12.3 (± 5.2)). Sample‐based rarefaction revealed that when only native tree species were pooled, the species richness was higher than for all tree species combined. The difference in species composition among tree species was strongly driven by bark and wood consumers in the first season, while for predators and fungivores, the differences were smaller. Species composition differed most in the first season. Dissimilarity in beetle species composition was positively correlated with phylogenetic distances of the tree species. Species richness was lower in non‐native tree species that are only remotely related to native trees species. Of the studied non‐native tree species, lodgepole pine was more closely related to native tree species and consistently harboured higher species richness. Synthesis and applications. Although non‐native tree species also harbour saproxylic beetle communities, the use of non‐native tree species, especially those only remotely related to native tree species, reduces local diversity of saproxylic beetles. Thus, for biodiversity conservation, an extensive use of non‐native tree species is not recommended as this increases the risk of losing forest biodiversity, especially when they are only distantly related to native tree species. Abstract : Although non‐native tree species also harbour saproxylic beetle communities, the use of non‐native tree species, especially those only remotely related to native tree species, reduces local diversity of saproxylic beetles. Thus, for biodiversity conservation, an extensive use of non‐native tree species is not recommended as this increases the risk of losing forest biodiversity, especially when they are only distantly related to native tree species.